Al torno de los conceptos del realismo mágico y lo real maravilloso - intento de diferenciación - Charchalis, Wojciech (Studia Romanica Posnaniensia, 2007)
The article presents some notes about the nature of the magic realism that can become useful to formulate a homogeneous definition of the concept. The basic differences between the concepts of magic realism and “lo real maravilloso” of Alejo Carpentier are also exposed. Those terms are frequently erroneously equalled by the critics which generates a terminological confusion that should be cleared. The magic realism is presented as an aesthetic term whereas “lo real maravilloso” is considered as an ontological term, which constitutes the main difference between them.